Effects of triterpenoids from Luvunga scandens on cytotoxic, cell cycle arrest and gene expressions in MCF-7 cells - Bakhtiar, M. Taher; Al-Zikri, Putri Nur Hidayah; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari; Rezali, Mohd Fazlin (The Korean Society of Pharmacognosy, 2016)
Plant-derived triterpenoids commonly possesses biological properties such as anti-inflammatory, antimicrobial, anti-viral and anti-cancer. Luvunga scandens is one of the plant that produced triterpenoids. The aims of the study was to analyze cell cycle profile and to determine the expression of p53 unregulated modulator of apoptosis (PUMA), caspase-8 and caspase-9 genes at mRNA level in MCF-7 cell line treated with two triterpenoids, flindissol (1) and 3-oxotirucalla-7,24-dien-21-oic-acid (2) isolated from L. scandens. The compounds were tested for cell cycle analysis using flow cytometer and mRNA expression level using quantitative RT-PCR. The number of MCF-7 cells population which distributed in Sub G1 phase after treated with compound 1 and 2 were 7.7 and 9.3% respectively. The evaluation of the expression of genes showed that both compounds exhibited high level of expression of PUMA, caspase-8 and caspase-9 as normalized to β-actin via activation of those genes. In summary, the isolated compounds of L. scandens plant showed promising anticancer properties in MCF- 7 cell lines.